ENHANCING TRANSPARENCY AND ACCOUNTABILITY THROUGH DIGITALIZATION: A CASE STUDY ON THE USE OF THE E-SIAP BOS APPLICATION IN BOS FUND MANAGEMENT - Nasrun Naida (Accounting Journal of Ibrahimy (AJI), 2024)
This study investigates the influence of digitalization on the management of School Operational Assistance (BOS) funds to enhance the efficiency and accountability of financial reporting in the education sector. The research focuses on the effectiveness of technologies, such as the e-SIAP BOS application, in addressing public fund management challenges, including reporting delays, data inaccuracies, and transparency issues. Employing a qualitative approach, the study analyzes the implementation of digitalization by collecting data through in-depth interviews with key stakeholders and examining official documents. The findings indicate that digitalization significantly improves the speed and accuracy of financial reporting, enhances transparency and accountability, and ensures compliance with regulations. Proper implementation of digital technology is expected to enhance public financial management and foster public trust in government fund oversight. As a qualitative study, the data analysis utilized the interactive model of data analysis proposed by Miles and Huberman (1992), providing a comprehensive understanding of the observed phenomena.